2022
DOI: 10.1128/msystems.00169-22
|View full text |Cite
|
Sign up to set email alerts
|

Modeling-Guided Amendments Lead to Enhanced Biodegradation in Soil

Abstract: Providing the food requirements of a growing population comes at the cost of intensive use of agrochemicals, including pesticides. Native microbial soil communities are considered key players in the degradation of such exogenous substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Simulations can guide validation experiments' design by ranking potential solutions that outperform ‘trial and error’ based solutions. In a recent study, we have demonstrated that model‐guided manipulation strategies for enhancing the biodegradation of agrochemicals in the soil can outperform trial and error‐based biodegradation solutions (Dhakar et al, 2022). Similarly, data‐guided manipulation strategies can pave the way for the future development of practical protocols for maintaining long shelf life while reducing the dependency on pesticides and agrochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations can guide validation experiments' design by ranking potential solutions that outperform ‘trial and error’ based solutions. In a recent study, we have demonstrated that model‐guided manipulation strategies for enhancing the biodegradation of agrochemicals in the soil can outperform trial and error‐based biodegradation solutions (Dhakar et al, 2022). Similarly, data‐guided manipulation strategies can pave the way for the future development of practical protocols for maintaining long shelf life while reducing the dependency on pesticides and agrochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…The framework presented is designed to be used as a platform to generate educated hypotheses regarding bacterial function in a specific environment in conjunction with actual carbon substrates available in the particular ecosystem under study. The hypotheses generated provide a starting point for experimental testing required to gain actual, targeted and feasible applicable insights 38,42 . While recognizing its limitations, this framework is in fact highly versatile and can be used for the characterization of a variety of microbial communities and environments.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate representation of microbial metabolic networks depends on the origin of the genomes analyzed. To date, most studies attempting to model the microbiome of specific ecosystems by GSMM represent native species using corresponding genome sequences from public depositories, a process which is usually referred to as 16S-based genome imputation 26,35,37 . Genome recovery, or genome-resolved metagenomes, often referred to as Metagenomes Assembled Genomes (MAGs) allows one to obtain full genomes directly from metagenomes 38,39 .…”
Section: Introductionmentioning
confidence: 99%